Research on resource scheduling of reconfigurable optical networks for distributed services - LI Hui; MA Lei-ming; JI Yue-feng (Tongxin xuebao)
To provide customized services for concurrent distributed applications in optical networks, a load balanced multi-source multi-path parallel scheduling strategy was proposed, in which the network load and applications load are equally shared in different resources nodes. Simulation results validate that this strategy can effectively reduces the block ratio of distributed services compared with single-source single-path strategy and multi-source multi-path strategy. A testbed of reconfigurable optical network for distributed services is designed to validate the feasibility and effectively of the load balanced parallel scheduling strategy through an example of distributed GridFTP service. The experiment results show,considering the load balance of the application resources and network resources together, this strategy with can successfully decrease the process time of distributed services in grid system and improve system performance.